2018
DOI: 10.1371/journal.pone.0201021
|View full text |Cite
|
Sign up to set email alerts
|

The spinal NR2BR/ERK2 pathway as a target for the central sensitization of collagen-induced arthritis pain

Abstract: ObjectivePain management is a huge challenge in the treatment of rheumatoid arthritis (RA), and central sensitization is reportedly involved in the development of pain. The current study was undertaken to explore the possible role of N-methyl-D-aspartate receptors (NMDARs) in the spinal mechanism of central sensitization in RA using a collagen-induced arthritis (CIA) model.MethodsMechanical hypersensitivity was assessed in C57BL/6 mice, before and after the induction of CIA via administration of chick type II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The NR2B subunit also induces peripheral sensitization in long-term chronic pain. 76 These findings indicated that NR2B is a novel research target for IA pathogenesis and pain management.…”
Section: Expressions Of the Nr2b Subunit In Iamentioning
confidence: 94%
“…The NR2B subunit also induces peripheral sensitization in long-term chronic pain. 76 These findings indicated that NR2B is a novel research target for IA pathogenesis and pain management.…”
Section: Expressions Of the Nr2b Subunit In Iamentioning
confidence: 94%
“…However, this nociceptive effect was attributed to NMDA receptors on peripheral nerves rather than on keratinocytes ( Carlton et al, 1995 ; Ma and Hargreaves, 2000 ). NR2B is associated with nociceptive transmission in a series of pain models ( Qu et al, 2009 ; Liao and Xu, 2017 ; Nozaki et al, 2011 ; Xu et al, 2018 ). The expression of NR2B in the forebrain ( Zhuo, 2009 ; Li et al, 2009 ) and spinal cord ( Boyce et al, 1999 ) has been found to enhance central pain potentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the intrathecal injection of the ERK1/2 signalling pathway inhibitor PD98059 reduces the pain and the p-ERK1/2 induction in this OA model 66 . In the CIA-induced arthritis model the analgesia achieved by the intrathecal administration of tramadol also show the reduction in the p-ERK1/2 increase 68 . The spinal microglia and astrocytes were shown to play a critical role in development of the pain hypersensitivity, as they can dynamic modulate the activity of spinal neurons 69 , 70 .…”
Section: Discussionmentioning
confidence: 85%